Causes and Effects of Online Video Game Playing among Junior-Senior High School Students in Malang East Java - Eskasasnanda, I Dewa Putu (Komunitas, 2017)
Science and technology development causes a lot of changes in any fields including the form of popular games among the Junior and Senior High School students in Indonesia. The traditional games that are famous formerly have been replaced by the modern games like online video game. This article discusses the cause and effect of the online video game playing on the Junior and Senior High Schools students in Malang. This study reveal that students play video games online due to peers pressure; and  online video games are  liked because they are considered more modern, practical, realistic and varied. Initially,  students play online video games to relieve the fatigue due to studying at school, but subsequently, they are becoming addicted, and reach a condition that they find it  difficult to stop playing games. This condition will directly affect their achievement in school.